1979
DOI: 10.1002/aja.1001540209
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical localization of cations in the testis of the syrian hamster, utilizing potassium‐pyroantimonate

Abstract: Pyroantimonate has long been used as a cytochemical technique for the localization of cations. Although the technique was originally alleged to be specific for Na+, other cations, including Mg++, Ba++, Ca++, Zn++ and polycationic amines, form pyroantimonate precipitates. In seminiferous tubules treated with antimonate-osmium fixation, the nuclei of the Sertoli cells and germ cells contained precipitates. In regions of condensed chromatin the precipitates were dense while, in dispersed chromatin, precipitates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…In contrast to hamster (Gravis, 1979) and to ram spermatozoa, both human (Chandler & Battersby, 1976) and guinea-pig (Friend, 1977) spermatozoa appeared to have no aggregation of precipitate in the postacrosomal region which might indicate cytochemical differences between the species. Also, ram spermatozoa had no precipitate beneath the acrosome, unlike human (Chandler & Battersby, 1976) and hamster (Gravis, 1979) sperm cells, which might reflect differences in penetration by pyro¬ antimonate. This seems unlikely since it has been suggested that, when pyroantimonate is used with osmium fixation, its penetration rate is "adequate to preserve 'normal' cation distribution" (Simson & Spicer, 1975 (Chandler & Battersby, 1976).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast to hamster (Gravis, 1979) and to ram spermatozoa, both human (Chandler & Battersby, 1976) and guinea-pig (Friend, 1977) spermatozoa appeared to have no aggregation of precipitate in the postacrosomal region which might indicate cytochemical differences between the species. Also, ram spermatozoa had no precipitate beneath the acrosome, unlike human (Chandler & Battersby, 1976) and hamster (Gravis, 1979) sperm cells, which might reflect differences in penetration by pyro¬ antimonate. This seems unlikely since it has been suggested that, when pyroantimonate is used with osmium fixation, its penetration rate is "adequate to preserve 'normal' cation distribution" (Simson & Spicer, 1975 (Chandler & Battersby, 1976).…”
Section: Discussionmentioning
confidence: 90%
“…The sig¬ nificance of calcium in this site is not apparent but it is this region of the plasma membrane that initially fuses with the vitelline membrane (Yanagimachi 8c Noda, 1970;Bedford, 1972). In contrast to hamster (Gravis, 1979) and to ram spermatozoa, both human (Chandler & Battersby, 1976) and guinea-pig (Friend, 1977) spermatozoa appeared to have no aggregation of precipitate in the postacrosomal region which might indicate cytochemical differences between the species. Also, ram spermatozoa had no precipitate beneath the acrosome, unlike human (Chandler & Battersby, 1976) and hamster (Gravis, 1979) sperm cells, which might reflect differences in penetration by pyro¬ antimonate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various fixatives containing 2% potassium pyroantimonate (Komnick 1962;Gravis 1979) and various modes of fixation were tried. Mice were divided into groups (three or four mice in each group) for comparing the techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore we have examined the structural changes that appear in the uterine epithelium 1 day after injecting lead to mice in experimental delay of implantation. Since changes can be caused by a local deposition of lead in the uterine epithelium (Ljung et al 1984) or can be secondary to an effect in, for instance, the ovary (Wide 1983;Franks et al 1989), we also checked whether lead could be detected in the uterine epithelium 1 day after the injection, using X-ray microanalysis of the cation precipitates which appear after a potassium pyroantimonate fixation for electron microscopy (Komnick 1962;Gravis 1979). …”
Section: Introductionmentioning
confidence: 99%